Applications of digital signal processing methods in TOF calculation of ultrasonic gas flowmeter. (June 2021) - Ma, Jie; Xu, Ke-Jun; Jiang, Zhen; Zhang, Lun; Xu, Hao-Ran
Abstract: Ultrasonic gas flowmeters (UGFM) are extensively used in petroleum, chemical, natural gas and other fields because of their distinctive measurement advantages. As the core technology of the UGFM, digital signal processing technology determines its measurement accuracy and stability. This paper systematically reviews the signal processing methods for measuring the TOF (time of flight) based on the principle of time difference method. According to the stability of the feature information extracted by different digital signal processing methods, the advantages and disadvantages of each method are analyzed. Aiming at the problems of serious energy attenuation, weak echo signal amplitude, and low signal-to-noise ratio (SNR) when ultrasonic signal propagate in the gas, different signal processing methods are evaluated and compared from the aspects of calculation accuracy, response speed, anti-interference ability and sensitivity to parameter changes. Finally, some improvement ideas and directions for further research are proposed according to the analysis results. Highlights: Various digital signal processing methods are classified systematically. The digital signal processing methods of extracting starting points are introduced in detail. The digital signal processing methods of extracting feature points are introduced in detail. The methods of the same type and different types are compared from many aspects. Some improvement suggestions and directions worthy of future research are put forward.